Long-term clinical value and outcome of riociguat in chronic thromboembolic pulmonary hypertension. (March 2019) - van Thor, M.C.J.; ten Klooster, L.; Snijder, R.J.; Post, M.C.; Mager, J.J.
Abstract: Background: To improve clinical outcome, patients with inoperable and residual chronic thromboembolic pulmonary hypertension (CTEPH) can be treated with riociguat. The aim of this study is to explore long-term outcomes and to compare our 'real world' data with previous research. Methods: We included all consecutive patients with technical inoperable and residual CTEPH, in whom riociguat therapy was initiated from January 2014 onwards, with patients followed till January 2019. Survival, clinical worsening (CW), functional class (FC), N-terminal pro brain natriuretic peptide (NT-proBNP) and 6-minute walking distance (6MWD) were described yearly after riociguat initiation. Results: Thirty-six patients (50% female, mean age 64.9 ± 12.1 years, 54% WHO FC III/IV and 6MWD 337 ± 138 m could be included, with a mean follow-up of 2.3 ± 1.2 years. Survival and CW-free survival three years after initiation of riociguat were 94% and 78%, respectively. The 6MWD per 10 m at baseline was a significant predictor (HR 0.90 [0.83–0.97], p  = 0.009) for CW. At three years follow-up the WHO FC and 6MWD improved and NT-proBNP decreased compared to baseline. Conclusion: Our study confirms that riociguat is an effective treatment in patients with technical inoperable and residual CTEPH at long-term follow-up. Although our results are consistent with previous studies, more 'real world' research is necessary to confirm long-term results.